Macroinvertebrados bentônicos em lavoura de arroz irrigado sob efeito de fungicidas e inseticidas - Wandscheer, Alana Cristina Dorneles (2016)
The irrigated rice crop has economic and social importance for the state of Rio Grande do Sul. It is considered an environment rich in biological diversity, it is home for a range of animal communities, especially invertebrates. However, the intensive use of pesticides has led to concerns about the impact on non-target aquatic organisms. The objective in this study was to evaluate the effects of fungicides and insecticides currently used in irrigated rice crop on the community of benthic macroinvertebrate. For this, field and laboratory experiments were conducted. Two field experiments (seasons 2012/13 and 2013/14), in an experimental lowland area, in the Federal University of Santa Maria, RS, Brazil were carried out in 10m2 plots cultivated with rice plants and control plots with and without rice plants, with a water depth of 10 cm. The treatments: trifloxystrobin + tebuconazole (50 + 100 g a.i. ha-1), tricyclazole (225 g a.i ha-1), lambda-cyhalothrin + Thiamethoxam (15.9 + 21.1 g a.i ha-1) and diflubenzuron (19.2 g a.i ha-1) were applied as a single dose on rice plants at stage R3. Soil samples were collected to evaluate the richness and density of benthic macroinvertebrate fauna. Physical and chemical water parameters such as temperature, pH and dissolved oxygen, and the persistence of pesticides in water and soil were evaluated during the experiments. The sample sufficiency for studies of the benthic macroinvertebrate community in rice crop areas was set. Two laboratory tests were carried out to complement the field studies. The first experiment aimed to verify the cytotoxic and genotoxic effects of tricyclazole through the bioindicator Allium cepa and the second experiment, aimed to verify the acute toxicity of the lambda-cyhalothrin and thiamethoxam active ingredients, alone and in combinations, on the species Chironomus dilutus organisms. The results showed that the establishment of the benthic macroinvertebrate community is favored in the natural environment without pesticides and rice plants. However, the application of a single dose of trifloxystrobin + tebuconazole fungicides and tricyclazole and lambda-cyhalothrin insecticide thiamethoxam + diflubenzuron causes no significant effects on the macroinvertebrate richness and density. Tebuconazole, tricyclazole and thiamethoxam had high persistence in irrigation water of the rice crop. Also, tricyclazole increased the genotoxic activity in the irrigation water of the rice crop, through the emergence of chromosomal alterations, without, however, causing significant effects on the mitotic index. The tested doses of lambda-cyhalothrin pyrethroid and thiamethoxam neonicotinoid, alone or in combinations, did not cause significant changes on organisms of the species Chironomus dilutus in laboratory studies.